The regulatory burden in the Swiss wealth management industry - Christian Buehrer; Ivo Hubli; Eliane Marti (Universität Zürich, Institut für schweizerisches Bankwesen, 2005)
[Introduction] In the recent past, regulatory costs have received a great deal of attention within the Swiss wealth management industry. On the one hand, financial institutions are intensifying their focus on cost management in general, due to the plunge of fees and commissions since the bubble burst on global equity markets. On the other hand, wealth management institutes are faced with rapidly increasing regulatory requirements, leading to a significant rise in their regulatory costs. Neither in theory nor in practice is there any doubt regarding the economic rationale and the necessity for regulation in the financial industry. Basically, bank regulation is justified as a means of preventing potential market failures in the financial sector, in order to protect depositors and the financial system as a whole: the characteristics of the wealth management business, such as agency problems and asymmetric information, may lead to risky behaviour on the part of wealth management institutes and potential losses for depositors and investors. A crisis in a single financial institute may easily lead to a crisis of confidence in the whole sector, with harmful consequences on monetary transactions and other industries within an economy. Additionally, regulators and supervisors are paying to attract attention to protecting the reputation of the financial industry and financial centres. The prevention of activities such as money laundering and the financing of terrorism is of paramount importance within this context. Yet, despite the positive effects of these regulatory interventions, their cost has to be considered, too. In fact, it is only if the overall benefits of regulation exceed its cost that regulation ultimately yields a profit. Attempts to quantify the cost of regulation can be found in the U.S. and the U.K. In Switzerland, however, there is still a lack of information on the regulatory burden of financial institutions.
Keywords: 330; Finanzdienstleistung; Regulierung; Regulierungstheorie; Schweiz